2005
DOI: 10.1136/ard.2003.019034
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of productivity loss in early rheumatoid arthritis: a 5 year follow up study

Abstract: Objective: To explore baseline risk factors for productivity loss and work disability over 5 years in patients with early, active RA. Patients and methods: In the FIN-RACo trial, 195 patients with recent onset RA were randomised to receive either a combination of DMARDs with prednisolone or a single DMARD for 2 years. At baseline, 162 patients were working or available for work. After 5 years' follow up, data on sick leave and retirement were obtained from social insurance registers or case records. The cumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 13 publications
8
75
1
2
Order By: Relevance
“…Data from the same cohort studies mentioned in more than one article have only been presented once in the final results. This applies to the articles of Reisine (7,22) and Puolakka (23,24). Chung et al (25) described two cohort studies (Nashville/Jyväs-kylä) in one article, but we presented the results as two studies.…”
Section: Selection and Methodological �Uality Assessmentmentioning
confidence: 98%
See 4 more Smart Citations
“…Data from the same cohort studies mentioned in more than one article have only been presented once in the final results. This applies to the articles of Reisine (7,22) and Puolakka (23,24). Chung et al (25) described two cohort studies (Nashville/Jyväs-kylä) in one article, but we presented the results as two studies.…”
Section: Selection and Methodological �Uality Assessmentmentioning
confidence: 98%
“…In employees with rheumatoid arthritis, various factors related to impaired body function or body structures have been found to be predictive of work disability. A moderate positive relation has been found between the presence of a rheumatoid factor (RF+) and work disability: four studies found a positive relation (35)(36)(37)(38) and four studies found no relation (24,25,(39)(40). The amount of deformed and swollen joints has been found to be a moderate positive prognostic factor for work disability: three studies found a positive relation between the amount of deformed joints and work disability (22,35,41), and four studies found no effect (7,24,26,42).…”
Section: Prognostic Factors For Work Disabilitymentioning
confidence: 99%
See 3 more Smart Citations